THE ABILITY OF Lactiplantibacillus plantarum TSD-10 AND DR-162 TO REDUCE AFLATOXIN AND MICROBIAL CONTAMINATION OF CORN - Rusli Fidriyanto; Roni Ridwan; Rohmatussolihat Rohmatussolihat; Wulansih Dwi Astuti; Yashanti Berlinda Paradisa; Ki Ageng Sarwono; Ainissya Fitri; Yantyati Widyastuti (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
Feed safety becoming the main factor to produce good quality food. The purpose of this study was to evaluate the ability of lactic acid bacteria in degrading aflatoxin B1, suppressing the growth of contaminant bacteria, and its application on feed. Biological degradation of aflatoxin B1 (AFB1) in liquid cultures and Escherichia coli and Saccharomyces aureus inhibition by Lactobacillus plantarum were examined. Fermentation of corn for 24 hours by L. plantarum was used to determine the ability of LAB to decrease E. coli, coliform, mold, and AFB1 on a solid substrate. This study showed that both L. plantarum TSD-10 and DR-162 could inhibit E. coli growth at 3% and 5% supernatant addition. The addition of 5% L. plantarum DR-162 and TSD-10 could inhibit S. aureus at 97.40% and 97.28%, respectively. Furthermore, viable cells of L. plantarum DR-162 and TSD-10 removed 56.97% and 64.65% AFB1 within 72 h of incubation, respectively. The AFB1 reduction by nonviable cell was lower than the viable cell. The population of E. coli, coliform, and mold completely disappeared in both fermentation treatment of corn by L. plantarum DR-162 and TSD-10 at 3% and 5%. AFB1 significantly decreased by 17.57% and 22.60% on 5% L. plantarum DR-162 and TSD-10 treatment.